2016
DOI: 10.1111/pedi.12376
|View full text |Cite
|
Sign up to set email alerts
|

Bias in food intake reporting in children and adolescents with type 1 diabetes: the role of body size, age and gender

Abstract: in food intake reporting in children and adolescents with type 1 diabetes: the role of body size, age and gender. Pediatric Diabetes 2017: 18: 213-221.Background: An assessment of total daily energy intake is helpful in planning the overall treatment of children with type 1 diabetes (T1D). However, energy intake misreporting may hinder nutritional intervention. Aims: To assess the plausibility of energy intake reporting and the potential role of gender, body mass index (BMI) z-score (z-BMI), disease duration a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 29 publications
0
6
0
Order By: Relevance
“…However, the ACAES has been validated and used in a number of other nutrition studies very similar to ours . Furthermore, it has been found that bias in food reporting in children with T1D is, on average, of modest magnitude . The control group was also made up of some siblings of children with T1D, which could impact the comparison between children with and without T1D as they may have been eating similar diets in the same household.…”
Section: Discussionmentioning
confidence: 71%
“…However, the ACAES has been validated and used in a number of other nutrition studies very similar to ours . Furthermore, it has been found that bias in food reporting in children with T1D is, on average, of modest magnitude . The control group was also made up of some siblings of children with T1D, which could impact the comparison between children with and without T1D as they may have been eating similar diets in the same household.…”
Section: Discussionmentioning
confidence: 71%
“…The families who adopt low carbohydrate diets, as in this case series, are often well educated, yet rely on personal blogs from social media as evidence that such a diet is in the best interest of their child. Furthermore, while under‐reporting of food intake should be considered in any assessment of the nutritional intake of children and adolescents with diabetes, families who follow restricted carbohydrate diets often fastidiously monitor carbohydrate intake. Health professionals face a predicament between trying to maintain a positive patient relationship, while trying to convince the family that the diet may be detrimental to their child's health.…”
Section: Discussionmentioning
confidence: 99%
“…However, energy intake based on just one day would be insufficient to determine over- or underreporting given the wide day-to-day intake variation especially among adolescents [ 27 ]. Also, there is evidence that adolescents tend to underreport their intake, which becomes more pronounced as weight increases [ 28 , 29 ]. Since some of our participants skipped a meal during the day (6/42, 14%), this could partly explain why median intakes of energy for both groups were lower compared to the EER.…”
Section: Discussionmentioning
confidence: 99%